The Impact of Competence and Internal Control Systems on the Accountability of Village Fund Management - Junus Paulus Patty; Ann Zusan de Bell (Brilliant International Journal Of Management And Tourism, 2023)
According to Law Number 6 of 2014, the Village Fund is a fund that comes from the state revenue and spending budget and is designated for villages. It is used to finance the implementation of governmental operations, development, community empowerment, and implementation. Accountability for money management is a type of community accountability for village government. The goal of this study was to investigate and analyze the effects of organizational commitment, internal control systems, apparatus competency, and community involvement on the accountability of village budget administration in Sirimau District, Ambon City.By providing respondents with questionnaires, this study collects primary data. The study's participants were 77 respondents from 14 villages in Sirimau District, Ambon City, who were village administrators and community members involved in administering village finances. In this work, multiple linear regression analysis was employed as the data analysis tool together with saturated sampling, also known as census sampling, using the SPSS 23 software.The study's findings demonstrate the influence of organizational commitment, internal control mechanisms, apparatus competency, and community involvement on the responsibility of managing village funds.